CHILDHOOD IMMUNIZATION COVERAGE IN URBAN SLUMS OF BAHAWALPUR CITY - Samina Badar; Siddique Khan Qadri; Muhammad Saleem Shaikh (Journal of University Medical & Dental College, 2016)
ABSTRACT: OBJECTIVE:The main objective of the study was to assess the immunization coverage in children 12-23 months of age in urban slums of Bahawalpur City. METHODOLOGY: A cross sectional descriptive study was conducted in slum areas of Bahawalpur City from July 2014 to December 2014 to assess the vaccination coverage of children less than 12-23 months of age after ethical approval of Institutional review board. Sample size calculated for the survey at 95% level of confidence, 5% margin of error and anticipated population proportion of 71.9%6 was 306. A multistage sampling technique was used for the survey. At first stage one slum area out of total 11 was selected by simple random method was Tibba Badar Sher and in second stage the households within area were selected by systematic random sampling technique. A preformed questionnaire (translated in local language) used to collect the data comprised of two parts. First part consists of sociodemographic variables of parents and second part was about the status of vaccination. The data was collected from mother/father of child present at home at the time of survey. Immunization status of child was assessed on the basis of immunization card. For those without immunization card information from mother/father were collected. The definitions for vaccination status were based on reception of injectable vaccines (BCG, pentavalent, pneumococcal and measles) because oral polio vaccine is provided on special polio days. No vaccination was defined as reception of no injectable vaccine included in the EPI schedule. Incomplete vaccination was defined as reception of at least one injectable vaccine but having not received all vaccines included in the EPI. Complete vaccination was defined as reception of all the injectable vaccines included in EPI in the first year of life. Data was entered and analyzed by using SPSS version 17. Chi square test was applied to see any statistical difference between the groups. P value ≤0.05 was taken as significant. RESULTS: Out of total 306 children surveyed, immunization card was available for only 26% children. Only 48% children completed their immunization while half were partially immunized. Among the individual vaccines the highest coverage was of BCG vaccine 86% followed by first dose of petavalent and pneumococcal vaccine (84%), second dose of petavalent and pneumococcal vaccine (78%). First dose of measles vaccine was received by 84% children while second dose coverage against measles was only 42%. Among children which had completed their immunization schedule 59.2% mothers had intermediate and above education and only 6.8% were illiterate while 50% mothers of non-immunized children were illiterate. Monthly family income of 74.1% children which received complete immunization was more than 20,000 and 83.3% children which were not immunized had monthly family income of less than 10,000. CONCLUSION: Our study results concluded that most of the children in 12-23 months of age are partially immunized.